Public Service Motivation Scholarship in Africa: A Systematic Review and Research Agenda - Bawole, J.N.; Mensah, J.K.; Amegavi, G.B. (International Journal of Public Administration, 2019)
Although several literature reviews have been published on public service motivation (PSM), none of them focused solely on Africa. Adopting a systematic review of the literature, we analyse articles on PSM scholarship in Africa published between 2005 and 2017. We found that authors in African PSM is consistently increasing with their research published in highly ranked peer-reviewed journals. The antecedents and consequences of African PSM are similar to those of Western countries. Finally, respondents of African PSM scholarship are skewed towards “managerist” and students’ perspective. We proposed agenda for African PSM research with four key interest areas.
Keywords: Public service motivation; African countries; Public management; Public administration; Literature review